2020
DOI: 10.21203/rs.2.18802/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic and physiological analyses of rice seedlings under different nitrogen supplies provide insight into the regulation involved in axillary bud outgrowth

Abstract: Background: N is an important macronutrient required for plant development and significantly influences axillary bud outgrowth, which affects tillering and grain yields of rice. However, how different N concentrations affect axillary bud growth at the molecular and transcriptional levels remains unclear. Results: In this study, morphological changes in the axillary bud growth of rice seedlings under different N concentrations ranging from low to high levels were systematically observed. To investigate the expr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…7c). Recently, the genes OsGS1;2 and OsGS2 were found to be highly expressed in the axillary buds under 5.0 mM nitrogen (Wang et al 2020), and further indicated that overexpression of OsGS1;2 and OsGS2 promote axillary bud growth and tiller number via ammonium assimilation, whereas reduced expression of GS1;2 affects the assimilation of ammonium into glutamine, resulting in decreased bud elongation and tiller number in rice (Ohashi et al 2015;Wang et al 2020). Similarly, our experiment also showed that expression of two genes OsGS1;2 and OsGS2 of the nitrogen pathway was increased in OE lines but decreased in Ri lines of OsAAP4.…”
Section: Discussionmentioning
confidence: 99%
“…7c). Recently, the genes OsGS1;2 and OsGS2 were found to be highly expressed in the axillary buds under 5.0 mM nitrogen (Wang et al 2020), and further indicated that overexpression of OsGS1;2 and OsGS2 promote axillary bud growth and tiller number via ammonium assimilation, whereas reduced expression of GS1;2 affects the assimilation of ammonium into glutamine, resulting in decreased bud elongation and tiller number in rice (Ohashi et al 2015;Wang et al 2020). Similarly, our experiment also showed that expression of two genes OsGS1;2 and OsGS2 of the nitrogen pathway was increased in OE lines but decreased in Ri lines of OsAAP4.…”
Section: Discussionmentioning
confidence: 99%